One-pot two-component synthesis of halogenated xanthone, 3-o substituted xanthone, and prenylated xanthone derivatives as aromatase inhibitors - Ramakrishnan, Shurutishria; Mad Nasir, Nadiah; Stanslas, Johnson; Faisal Hamdi, Amir Imran; Mohammad Latif, Muhammad Alif; Baharuddin, Fatin Farhana (Elsevier BV, 2023)
This study describes the synthesis, characterization, and biological activities of halogenated xanthone, 3-O substituted xanthone, and prenylated xanthone derivatives. The molecular structures of these compounds were identified using 1 H NMR, 13C NMR, 2D NMR, FTIR and DIMS. All synthesized compounds were evaluated against two cancer cell lines: breast adenocarcinoma MCF-7 and MDA-MB-231 by application of the MTT assay. With this approach, xanthones 9 and 13 were identified as putative aromatase activating agents through the inhibition of interactions with MCF-7 and MDA-MB-231. The selected compounds, 9 and 13, were further examined for toxicity against the African Green Monkey Kidney cell (VERO) and Non-tumorigenic Lung Epithelial cell lines (BEAS-2B). In addition, in-silico docking studies were conducted to estimate the binding poses and residues implicated in probable MCF-7 and MDA-MB-231 interactions.